1994
DOI: 10.1063/1.355924
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic etching of polymers in SO2/O2 plasmas: Hypotheses on surface mechanisms

Abstract: A study of the anisotropy of the etching of resists in SO2-based plasmas is performed in a distributed electron-cyclotron-resonance plasma excited at 2.45 GHz with independent radio frequency biasing at 13.56 MHz. Emphasis is put on the comparison of the profiles and etch rates obtained in pure oxygen and SO2-containing plasmas as a function of substrate temperature and ion bombardment energy. For a constant ion bombardment intensity, a significant decrease in the etch rate obtained using pure SO2 plasmas is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…This latter type of adsorption has already been observed when etching polymers with a oxygen-based chemistry. [20][21][22][23] Indeed, HBr/O 2 is a very chemical and spontaneous chemistry, which proceeds essentially through chemical reactions between the oxygen atoms present in the discharge and the resist. As the oxygen is very reactive with carbon, volatile etch products such as CO and CO 2 tend to form fast and spontaneously after the oxygen adsorption on the polymer surface, leading to fast trim rates driven by thin reactive layers.…”
Section: A Influence Of the O 2 Concentrationmentioning
confidence: 99%
“…This latter type of adsorption has already been observed when etching polymers with a oxygen-based chemistry. [20][21][22][23] Indeed, HBr/O 2 is a very chemical and spontaneous chemistry, which proceeds essentially through chemical reactions between the oxygen atoms present in the discharge and the resist. As the oxygen is very reactive with carbon, volatile etch products such as CO and CO 2 tend to form fast and spontaneously after the oxygen adsorption on the polymer surface, leading to fast trim rates driven by thin reactive layers.…”
Section: A Influence Of the O 2 Concentrationmentioning
confidence: 99%
“…Sulfur incorporation might also be desired for the passivation of organic materials in multilayer etch resist constructs. 8,9 Future studies of the interaction of SO 2 with these and other materials may provide valuable information about the controlled implantation of sulfur-containing functional groups and the retention of these functional groups over time for use in a variety of applications.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is worth noting that, in its own right, SO 2 has been considered as a useful etchant of polymeric materials in pattern transfer steps for multilayer resist technologies. [8][9][10][11] Although these systems proved to be effective for both etching and sidewall passivation of the polymeric resist material, the formation of sulfides on copper interconnects emerged as a deleterious side effect. 12 This highlights the importance of obtaining a chemically specific understanding of how reactive species behave in etch systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the oxygen plasmas could provide good etch capability on the organic dielectric (Hsu et al, 2000), as well as very high removal rate of the organic resist and the high etching selectivity over the polysilicon and gate oxide. Furthermore, it has been reported that N 2 , He, CHF 3 (Doemling, et al, 1998), Cl 2 (Kure et al, 1991;Sparks et al, 1992), HBr (Kure et al, 1991;Tokashiki et al, 1993), and SO 2 (Hutton et al, 1995;Pons et al, 1994) are also effective for dry development of resist.…”
Section: Introductionmentioning
confidence: 98%